2016
DOI: 10.5500/wjt.v6.i4.729
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Epstein-Barr viral load in Epstein-Barr viral naïve pediatric heart transplant recipients: Risk of late-onset post-transplant lymphoproliferative disease

Abstract: AIMTo examine the risk of late-onset post-transplant lymphoproliferative disorder (PTLD) in the presence of persisting high Epstein-Barr virus (EBV) in EBV naïve pediatric heart transplant (HT) recipients.METHODSA retrospective review of the medical records of the 145 pediatric HT recipients who had serial EBV viral load monitoring at our center was performed. We defined EBV naive patients whose EBV serology either IgM or IgG in the blood were negative at the time of HT and excluded passive transmission from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Persistently elevated high EBV viral loads measured in blood occurs commonly in solid organ transplant recipients, particularly those experiencing donor‐derived primary EBV infection; these patients are described as having a chronic EBV viral load phenotype . Interestingly, both immunocompetent and transplanted children infected with EBV at a very young age appear to have higher viral loads . This may make young children more vulnerable to concomitant or sequential PTLD and EBV‐SMT, as compared to their adult counterparts, which is also suggested by our review of the literature.…”
Section: Discussionsupporting
confidence: 60%
“…Persistently elevated high EBV viral loads measured in blood occurs commonly in solid organ transplant recipients, particularly those experiencing donor‐derived primary EBV infection; these patients are described as having a chronic EBV viral load phenotype . Interestingly, both immunocompetent and transplanted children infected with EBV at a very young age appear to have higher viral loads . This may make young children more vulnerable to concomitant or sequential PTLD and EBV‐SMT, as compared to their adult counterparts, which is also suggested by our review of the literature.…”
Section: Discussionsupporting
confidence: 60%
“…49 50 Chronic uncontrolled EBV reactivation has been shown to be an important factor in the pathogenesis of NPC 51 and PTLD. 52 It has been shown that an NPC-associated BZLF1 variant is associated with the enhancement of lytic EBV infection. 53 PTLD has also been shown to be associated with detectable circulating EBV genome and ZEBRA, the gene product of BZLF1.…”
Section: Lytic Phase Of Infectionmentioning
confidence: 99%
“…The chief risk factor for the development of EBV-SMT is believed to be high EBV viral load. 3 , 5 , 6 Although the mechanism of EBV-SMT is not known, one theory proposed that EBV entry into mesenchymal cells or their precursors may be mediated by high local levels of viremia without access to the B cell receptor CD21. 7 , 8 Once infected, EBV alters molecular signaling pathways, particularly the mechanistic target of rapamycin/Akt (also known as protein kinase B) pathway.…”
Section: Discussionmentioning
confidence: 99%